Propriedades ópticas e magneto-ópticas de monocamadas de dicalcogenetos de metais de transição - Soares Covre, Felipe (2022)
Bidimensional (2D) materials are systems of great interest both from the fundamental physical point of view and for possible applications in electronics, optoelectronics and spintronics. In this thesis, the optical properties of monolayers of transition metal dicalcogenetes (TMD) grown by Chemical Vapor Deposition (CVD) and exfoliated were investigated. In particular, we conducted a systematic study of the optical properties of tungsten disulfide (WS2) of large area (of the order of some cm), grown by van der Waals epitaxy on a CVD system. We investigated the optical properties of these samples using macro-photoluminescence and micro-photoluminescence techniques at low temperatures. We observed that the optical emission of these samples is quite unstable in time and that this optical instability depends on the temperature and power of the laser. This effect was associated with photo-induced doping. In addition, we observed thin peaks in the region of lower energy that are promising candidates for the generation of single photons. In general, the results obtained help to gain a greater understanding of the effects of photo-doping dynamics on these systems, which is important for future applications of TMD-based devices. We also investigated biaxial stress effects on a monolayer of molybdenum diselenide (MoSe2)/h-BN prepared by mechanical exfoliation and dry transfer technique. The sample studied has a region with a bubble of the order of 15 micrometers producing a mechanical biaxial tension of up to 1.3% in that region. We investigated the effects of tension using several experimental techniques, such as PL, magneto-PL and second harmonic generation (HGS). The results obtained showed the presence of a non-uniform tension in the sample, as well as a displacement to red in the PL peaks of the exciton and trion, when compared with the region without tension in the sample. A decrease of the trion binding energy and an increase in the g-factor of the trion and exciton in the bubble region were also observed. The results obtained are consistent with calculations of first principles performed in these systems. The results obtained present valuable information on stress effects in the properties of excitons and trions in MoSe2 monolayer and are interesting for the development of devices with controlled mechanical tension based on TMDs.